CAPSAICIN EXTRACTION FROM HOT PEPPERS (Spectrum Journal of Innovation, Reforms and Development, 2023)
The article studied the extraction process from hot pepper crop to develop a method for the analysis of capsaicin. Effects of extractant, hydromodulus and particle sire on carsaicin extraction rate and frequency were studied.